Making a slave state political development in early South Carolina - Quintana, Ryan A. (University of North Carolina Press, 2018)
"Beginning in the early eighteenth century and moving through the post-War of 1812 internal improvements boom, Quintana highlights the surprising ways enslaved men and women sat at the center of South Carolina's earliest political development, materially producing the state's infrastructure and early governing practices, while also challenging and reshaping both through their day-to-day movements, from the mundane to the rebellious. Focusing on slaves' lives and labors, Quintana illuminates how black South Carolinians not only created the early state, but also established their own extralegal economic sites, social and cultural havens, and independent communities along South Carolina's roads, rivers, and canals"...